2021
DOI: 10.1016/j.atmosenv.2020.117947
|View full text |Cite
|
Sign up to set email alerts
|

High rise in carbonaceous aerosols under very low anthropogenic emissions over eastern Himalaya, India: Impact of lockdown for COVID-19 outbreak

Abstract: The present study has been conducted to investigate the relative changes of carbonaceous aerosols (CA) over a high altitude Himalayan atmosphere with and without (very low) anthropogenic emissions. Measurements of atmospheric organic (OC) and elemental carbon (EC) were conducted during the lockdown period (April 2020) due to global COVID 19 outbreak and compared with the normal period (April 2019). The interesting, unexpected and surprising observation is that OC, EC and the total CA (TCA) during the lockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 54 publications
0
39
0
1
Order By: Relevance
“…Similarly, the increased organic aerosol fraction has been associated with larger values of AAE and SAE in Rome [105]. Chatterjee et al [106] reported higher SOA formation during the lockdown in the eastern Indian Himalayas due to reduced NO and high concentrations of O3 and biogenic VOCs, implying AAE values closely follow the 2016-2019 diurnal pattern, but they exhibit higher (within 10%) values during 2020 (Figure 7d-f. Despite this small relative increase, the AAE values during the lockdown period were at the upper limits of-or beyond-the shaded area that defines 1 standard deviation of the 2016-2019 mean.…”
Section: Changes In Diurnal Aerosol Patterns During Lockdown Pre-andmentioning
confidence: 73%
See 1 more Smart Citation
“…Similarly, the increased organic aerosol fraction has been associated with larger values of AAE and SAE in Rome [105]. Chatterjee et al [106] reported higher SOA formation during the lockdown in the eastern Indian Himalayas due to reduced NO and high concentrations of O3 and biogenic VOCs, implying AAE values closely follow the 2016-2019 diurnal pattern, but they exhibit higher (within 10%) values during 2020 (Figure 7d-f. Despite this small relative increase, the AAE values during the lockdown period were at the upper limits of-or beyond-the shaded area that defines 1 standard deviation of the 2016-2019 mean.…”
Section: Changes In Diurnal Aerosol Patterns During Lockdown Pre-andmentioning
confidence: 73%
“…Similarly, the increased organic aerosol fraction has been associated with larger values of AAE and SAE in Rome [105]. Chatterjee et al [106] reported higher SOA formation during the lockdown in the eastern Indian Himalayas due to reduced NO and high concentrations of O 3 and biogenic VOCs, implying that the site characteristics and the relative fraction between urban/anthropogenic and biogenic VOCs are especially important for the SOA formation processes during the lockdown period.…”
Section: Changes In Diurnal Aerosol Patterns During Lockdown Pre-andmentioning
confidence: 98%
“…They have observed an enhancement in heterogeneous uptake of SO 2 at RH levels more than 50%. Additionally, recent studies also reported the enhanced SOA formation because of O 3 increase during the lockdown ( Chatterjee et al, 2021 ). However, decrease in both O 3 and SO 2 have been observed at Gadanki.…”
Section: Discussionmentioning
confidence: 92%
“…Some authors found that during lockdown the ozone concentrations were higher than in normal situations, being this related with the increase of organic carbon and decrease of elemental carbon in aerosols [ 60 ].…”
Section: Pm 10 and Pm 25mentioning
confidence: 99%